2017
DOI: 10.1245/s10434-017-5774-x
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Shaving Reduces Involved Margins and Reinterventions Without Increasing Costs in Breast-Conserving Surgery: A Propensity Score-Matched Study

Abstract: CSM reduces reexcisions, mainly in luminal breast cancers, without increasing costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…It has not been shown to adversely affect cosmetic outcomes. Corsi et al found that avoiding cavity shaved margins expose patients to 6.2-fold higher risk of positive margin and 5.46-fold higher risk of reintervention (76). The cost effectiveness has been looked at, and there has been no increase in cost doing cavity shaves due to significantly fewer reoperations (77).…”
Section: Updatementioning
confidence: 99%
“…It has not been shown to adversely affect cosmetic outcomes. Corsi et al found that avoiding cavity shaved margins expose patients to 6.2-fold higher risk of positive margin and 5.46-fold higher risk of reintervention (76). The cost effectiveness has been looked at, and there has been no increase in cost doing cavity shaves due to significantly fewer reoperations (77).…”
Section: Updatementioning
confidence: 99%
“…Oncologic surgeons typically approach this by excising a volume of tissue slightly larger than that of the target tumor to obtain an outer layer of presumably healthy tissue known as the tumor margin. The surgeon may also take additional margin of tissue shaved from the walls of the cavity created by the tumor [4][5][6]. If, on postoperative analysis, the pathologist determines the margins to be free of cancerous cells to a depth of 2 mm or more from the main tumor for DCIS, and no ink on tumor for invasive cancer, then the chances of local disease recurrence are relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Only direct medical costs were reported; indirect costs (not directly accountable to the operation) and intangible costs (unquantifiable cost relating to an identifiable source) were not estimated in any of the reviewed literature. The source of cost estimates was hospital records in four studies and Centers for Medicare and Medicaid Services reimbursement data in three. Initial BCS and reoperation costs were in the range US $1234–11786 and $655–9136 respectively ( Table S2, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…The present health economic review highlights the heterogeneity and paucity of high‐quality studies reporting cost estimates of reoperations in breast surgery. Only nine studies have commented on reported costs of re‐excision in BCS, with two employing a predictive model to hypothesize the cost impact of re‐excision following BCS in the USA and Canada. Several studies contained minimal cost information, whereas others reported a range of costs for numerous variables that could not be collated accurately.…”
Section: Discussionmentioning
confidence: 99%